Academic Perspectives on the Gayo-Language Translation of the Qur’an - Saleh, Fauzi; Johansyah, Johansyah; Lukman Hakim; Fata Zakir (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2026)
This study examines the perspectives of academics on the Gayo-language translation of the Qur’an as an effort to preserve local wisdom, while also identifying the challenges surrounding its production and use. The translation of the Qur’an into regional languages, particularly Gayo, holds a strategic position in safeguarding linguistic and cultural heritage; however, such efforts have not yet received sufficient academic attention. This research employs a qualitative approach, with data collected through document analysis and in-depth interviews. The data are analyzed using a sociolinguistic framework. The findings reveal three main points. First, academics view the Gayo Qur’anic translation as a form of tafsīr-based (interpretative) translation that reflects rational interpretation and is strongly influenced by Gayo cultural context, especially in diction and stylistic choices. Second, several challenges are identified, including achieving semantic accuracy in the target language, ensuring conformity with the intended meanings of Qur’anic verses, and addressing readers’ linguistic preferences and accessibility. Third, academics propose several solutions, such as maximizing reference to authoritative Qur’anic commentaries, considering the historical context of revelation (asbāb al-nuzūl), and adapting to ongoing developments in local linguistic usage.